Individuals with Borderline Personality Disorder manifest cognitive biases implicated in psychosis. (September 2018) - Puri, Priya; Kumar, Devvarta; Muralidharan, Kesavan; Kishore, M. Thomas
Highlights: Individuals with Borderline Personality Disorder (BPD) manifest cognitive biases implicated in the formation and maintenance of psychotic symptoms, especially delusions. Comorbidity(ies) do not affect the severity of these cognitive biases in individuals with BPD. These findings have important implications from the perspective of psychotherapy for BPD. Abstract: Individuals with Borderline Personality Disorder (BPD) frequently manifest psychotic symptoms. Certain cognitive biases have been implicated in the genesis and maintenance of psychotic symptoms. The present study aimed at exploring whether individuals with BPD manifest these cognitive biases. Twenty-eight individuals with BPD and 28 healthy participants were assessed on four sub-domains of the Davos Assessment of Cognitive Biases Scale, viz. jumping to conclusions, belief inflexibility, attention for threat and external attribution. The BPD group had significantly higher scores on all the four cognitive biases in comparison to the healthy controls. Thus, the findings of the present study indicate that individuals with BPD manifest cognitive biases implicated in psychosis more prominently than healthy individuals. These findings can be used to improve the existing psychotherapeutic techniques for BPD.